2020
DOI: 10.1007/s13555-020-00414-7
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Micro-Dosing of AbobotulinumtoxinA for Face-Lifting: How Long Does It Last?

Abstract: Introduction Intradermal injection of botulinum toxin type A (BoNT/A) has been used off-label by many clinicians for face-lifting. Previous studies on abobotulinumtoxinA (ABO) (Dysport®; Ipsen Biopharm Ltd.) have demonstrated clinical efficacy in face-lifting when compared to normal saline solution (NSS). However, few clinical studies have evaluated ABO in terms of duration of sustained effects for face-lifting. Methods Thirty subjects were enrolled, and their face was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…24 Indeed, when injections were performed along the hair and jawlines, this somewhat created face-lift–like vectors, which probably accounts for some semblance of the face-lifting effect observed. 11–13,15 Finally, while the dilution, concentration, type, and total dose of botulinum toxin used were all highly varied in this study, analysis of results suggest that an average of 20 to 30 BU (or equivalent) would produce a face-lifting effect, provided the injection patterns were designed to recreate face-lift vectors, sort of, as mentioned. It does seem, however, that injecting with 30-G needles resulted unanimously in procedure-related pain, 9,15 whereas studies that utilized 32-G needles only reported minimal bruising in 13.8% of patients, 13 so this may be worth bearing in mind.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…24 Indeed, when injections were performed along the hair and jawlines, this somewhat created face-lift–like vectors, which probably accounts for some semblance of the face-lifting effect observed. 11–13,15 Finally, while the dilution, concentration, type, and total dose of botulinum toxin used were all highly varied in this study, analysis of results suggest that an average of 20 to 30 BU (or equivalent) would produce a face-lifting effect, provided the injection patterns were designed to recreate face-lift vectors, sort of, as mentioned. It does seem, however, that injecting with 30-G needles resulted unanimously in procedure-related pain, 9,15 whereas studies that utilized 32-G needles only reported minimal bruising in 13.8% of patients, 13 so this may be worth bearing in mind.…”
Section: Discussionmentioning
confidence: 82%
“…Vectra) to evaluate changes in facial volume as a surrogate measure for a face-lifting effect. 12,13 Follow-up was from as early as 1 week and averaged up to 10.5 (range, 1-24) weeks after treatment. Overall, in general, patients tended to self-report a more positive face-lifting effect as compared with that by a blinded physician (Figure 1).…”
Section: Highly Variable Assessment Of Treatment Outcomesmentioning
confidence: 99%
“…The intradermal injection technique, otherwise known as the “micro‐botulinum” technique, involves serial injection of tiny aliquots of BTX just under the skin surface 13,14 15,16 …”
Section: Introductionmentioning
confidence: 99%
“… 2 Blocking the secretion of calcitonin gene-related peptide and vasoactive interstitial peptides has been shown to reduce flushing, induce collagen synthesis, and improve skin texture. 3 …”
mentioning
confidence: 99%
“…BTX-A manufacturers recommend sterile physiological saline as a standard dilution solution, but more recent studies have shown that dilution with lidocaine is an effective way to reduce pain. 3 However, because the pH of lidocaine solution is about 6, it is weakly acidic and inevitably causes pain during injection. Therefore, mixing lidocaine with sodium bicarbonate increases the pH to 7.2, reducing the pain.…”
mentioning
confidence: 99%